Las competencias emocionales y la práctica docente en la mitigación de los conflictos escolares (2020)
The education of emotions in recent years has gained great importance, due to its impact on the social, and also academic performance of children and young people. The present research entitled "Emotional competencies and teaching practice in the mitigation of school conflicts", has the general purpose of interpreting the emotional competencies of the teacher, and the strategies available to mitigate and prevent interpersonal conflicts between school peers. Carried out under a qualitative methodology study, with a phenomenological approach, according to Van Manen, where Emotional Competencies and teaching practice are investigated in the mitigation of school conflicts in preschool and elementary school teachers of a private and confessionally Catholic institution, belonging to the community of the De La Salle Brothers. 11 classroom teachers, 2 teaching directors and a school counselor participated. The study aims to reveal the complexity of the phenomenon, based on the meanings that people attribute to the focus of the research, the possible obstacles, and the needs that emerge within an instrumentalized society. After the application of the research instruments, a hermeneutical work was carried out to give meaning to the voices of the actors in the face of this phenomenon and it was concluded that it is urgent in the school context to equip teachers with strategies that can from the Emotional Competences to strengthen the teaching practice for the prevention and mitigation of school conflicts.